Feasibility analysis of lateral water interception curtain in loose aquifer during deep coal seam mining in Yushen mining area - Chunhu ZHAO; Shidong WANG; Zhongkui JI; Kaipeng ZHU; Xiangyang LIANG (Meitan xuebao)
Yushen mining area is the main mining area of the coal base in northern Shaanxi at present. During the development of high-intensity coal resources, the problems of coal seam roof water disaster and water resource leakage are prominent. with the comprehensive promotion of the ecological environment protection strategy in the Yellow River Basin, advanced, proactive, and source oriented geological guarantee requirements have been put forward for mine water prevention and water resource protection. the article focuses on the problem of water inrush (loss) in the loose water bearing layer near the surface under the influence of underground coal mining in Yushen mining area, Shaanxi Province. Drawing on the successful experience of curtain seepage reduction in open-pit large water mining areas, the article summarizes the basic conditions for carrying out underground continuous wall water interception curtains in coal mining areas from three aspects: stable supply water sources, relatively concentrated supply channels, and the waterproof layer conditions to prevent groundwater from flowing around; a theoretical model of water inflow under the condition of loose water rich aquifer curtain in underground coal mines is established. It is concluded that the weaker the permeability and thickness of the cut-off curtain wall, and the closer it is to the mining range, are the basic principles for reducing water inrush in the loose aquifer near the surface of the coal seam roof. Taking the problem of concentrated water inflow in a coal mining face in Yushen mining area as the research object, based on the basic principle of groundwater continuous wall curtain seepage reduction, it is analyzed that the main water source in the concentrated water inflow section of the working face is the loose aquifer groundwater near the surface, which has stable and observable dynamic recharge. The water conducting cracks formed by coal seam mining break through the roof waterproof soil layer and expose the strip-shaped ancient river channel inside the loose layer (the waterproof soil layer inside the ancient river channel becomes thinner and the loose layer becomes thicker), forming a relatively concentrated water inflow channel. Under the combination structure of "upper aquifer and lower barrier" (the upper layer is the rich water loose aquifer, and the lower layer is the relatively waterproof soil layer), it is believed that this section has the feasibility of constructing a lateral waterproof curtain wall. and a numerical model of the groundwater system was established for the working face under normal mining and curtain wall construction conditions. The simulation results showed that under local curtain wall conditions around the working face, the groundwater level gradient in the loose aquifer around the curtain wall was significantly intensified. However, due to the good permeability of the loose aquifer and the low terrain and water control conditions of the mining field, the groundwater level in the loose layer near the ground did not significantly rise. The groundwater runoff that entered the goaf through the thin bedrock area and the thickened strip of the loose layer was diverted downstream, and The overall water reduction rate under the construction conditions of a 600 m long lateral cut-off curtain wall is 28.43%. The research results of the article provide a scientific basis for the feasibility analysis of roof water damage prevention and groundwater resource protection based on water interception curtains in the Jinggong Coal Mine of Yushen Mining Area.